THE EFFECT MODEL INQUIRY TRAINING MEDIA AND LOGICAL THINKING ABILITY TO STUDENT’S SCIENCE PROCESS SKILL - Dahrim Pohan (Jurnal Pendidikan Fisika, 2017)
The aim of the research is to analyz : student’s science process skill using inquiry training learning model is better than konvesional learning.Student’s science process skill who have logical thinking ability above average are better than under average,and the interaction between inquiry training media and logical thinking ability to increase student’s science process skill.The experiment was conducted in SMP 6 Medan as population and class VII-K and VII-J were chosen as sample through cluster random sampling.Science prosess skill used essay test and logical thinking used multiple choice as instrument.Result of the data was analyzed by using two ways ANAVA.Result show that : student’s science process skill using inquiry training learning model is better than konvesional learning,student’s science process skill who logical thinking ability above average are better than under average and the interaction between inquiry training learning model media and logical thinking ability to increase student’s science process skill.